Current conceptualizations of narcissism. Issue 1 (January 2019) - Ackerman, Robert A.; Donnellan, M. Brent; Wright, Aidan G.C.
Abstract : Purpose of review: Definitions of narcissism have traditionally differed across psychiatry and subfields of psychology. This review aims to highlight emerging points of consensus and suggest further directions needed to obtain a more comprehensive and cohesive conceptualization of the construct. Recent findings: An emerging consensus is that stable individual differences in the phenotypic expression of narcissism are best captured with a taxonomy that includes the core traits of entitlement, grandiosity, and vulnerability. Recent work has also begun to conceptualize and assess narcissistic states matched with these dimensions. We combine emerging taxonomic knowledge with principles from Whole Trait Theory to propose a multilevel conceptualization of narcissism that focuses on its manifestation at the trait level, state level, and within-situation level. Summary: Efforts to understand the phenotypic structure of the core traits associated with narcissism have been successful. As the field moves forward, it will become critical for researchers studying narcissism at multiple levels to align and integrate these perspectives so that a more comprehensive and cohesive conceptualization of the construct can be developed.